1997
DOI: 10.1113/jphysiol.1997.sp021922
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of cardiovascular, endocrine and behavioural effects of betamethasone and dexamethasone administration to fetal sheep.

Abstract: induce similar increases in fetal blood pressure and similar falls in the incidence of fetal breathing movements. The pronounced betamethasone-induced fetal hypertension is associated with an increase in fetal femoral vascular resistance.Antenatal glucocorticoid administration to enhance fetal periventricular haemorrhage and necrotizing enterocolitis lung maturation has been used in obstetric practice over the (Crowley, Chalmers & Keirse, 1990). Thus, the National last 20 years since first reported by Liggins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
134
1
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(149 citation statements)
references
References 29 publications
13
134
1
1
Order By: Relevance
“…In previous studies, high doses of glucocorticoids administered for a short time to the fetal sheep increase blood pressure to a similar extent to that seen in this study, with no change in heart rate (Hill et al 1988, Derks et al 1997. In addition, it has been reported that dexamethasone treatment to pregnant rats during the last third of gestation produces elevated blood pressure in the offspring (Levitt et al 1996).…”
Section: Blood Pressuresupporting
confidence: 47%
“…In previous studies, high doses of glucocorticoids administered for a short time to the fetal sheep increase blood pressure to a similar extent to that seen in this study, with no change in heart rate (Hill et al 1988, Derks et al 1997. In addition, it has been reported that dexamethasone treatment to pregnant rats during the last third of gestation produces elevated blood pressure in the offspring (Levitt et al 1996).…”
Section: Blood Pressuresupporting
confidence: 47%
“…Adrenergic cardiovascular drive and noradrenergic infl uences play a key role in the development or progression of hypertension and the metabolic syndrome in the adult (Grassi et al, 2009), making this system another key candidate for glucocorticoid induced long-term alterations in system balance. This notion is supported by experiments showing a sustained elevation of blood pressure and altered baroreceptor heart rate response in fetal sheep and the baboon and increased central and peripheral vascular resistance after glucocorticoid administration (Derks et al, 1997;Fletcher et al, 2002;Koenen et al, 2002;Schwab et al, 2000). 6.5 HPA axis functionality in neonates after intrauterine betamethasone treatment Η 53…”
Section: Vulnerability Of the Sympathetic Nervous Systemsupporting
confidence: 59%
“…the age at which most fetuses were monitored in the present study. In addition, no changes were found in limb movements and nuchal muscle activity after betamethasone infusion into the fetal sheep (19). So, whether or not the increases in ACC are due to increased fetal bodily activity awaits further direct ultrasound observation.…”
mentioning
confidence: 99%
“…The decrease in FHR generally occurred within one to several hours after the start of corticosteroid administration, indicative of involvement of nongenomic glucocorticoid receptors (GR), and was associated with an increase in arterial blood pressure (17)(18)(19)(20)(21). The latter is a known effect of corticosteroids and is assumed to result from increased peripheral vascular resistance (22,23).…”
mentioning
confidence: 99%